Peranan Hukum dalam Meningkatkan Pembangunan - Sebayang, Supriyadi (Jurnal Indragiri Penelitian Multidisiplin, 2024)
Law plays an important role in development. Law is essential to form a framework to achieve fair and sustainable development goals. Without an adequate legal system, development will be vulnerable to uncertainty. In addition, in a legal climate full of uncertainty, it is full of potential conflicts and abuse of community rights. Ultimately, the threat of development failure will become more real. Likewise, in the context of economic recovery, the role of law is very important, at least it can be used as a momentum to be able to display law with its corrective role, correcting and improving the behavior (especially) of state administrators and various policies that can affect the economic sector. The corrective role of law at least covers areas that can support development and welfare, such as economic stability, social, Human Rights and a sustainable environment (sustainability). Law also plays an important role in ensuring social justice and equal distribution of welfare in the midst of the economic development process. In addition, a strong legal system can create a conducive investment climate by providing certainty and protection for business actors. Furthermore, effective law can encourage innovation and creativity in the economic sector by protecting intellectual property rights and supporting healthy business competition. The law also has an important function in regulating and supervising the financial sector, including banking and capital markets, to prevent detrimental practices and maintain the stability of the financial system. In addition, the role of law in economic recovery includes providing a regulatory framework that supports the development of sustainable and environmentally friendly industries.